PENGGUNAAN KOMBINASI PUPUK NPK DENGAN PUPUK PELENGKAP CAIR (PPC) PADA TANAMAN CABAI RAWIT (Capsicum frustescens) - Novia, Masita; ', Armaini; ', Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to determine the best combination of NPK with liquid complement fertilizer, in the growth and production ca’yenne pepper. The research was carried out experimentally using Completely Randomized Design (CRD) with 6 treatments and 4 replications so that there are                      24 experimental units and each unit consists of three plants, so that population ca’yenne pepper was 72 plants. The treatment consists P1: 100 kg NPK/Ha with   1 g PPC/1l water, P2: 100 kg NPK/Ha with 2 g PPC/1l water, P3: 150 kg NPK/Ha with 1 g PPC/1l water, P4: 150 kg NPK/Ha with 2 g PPC/1l water,                        P5: 200 kg NPK/Ha with 1 g PPC/1l water, P6: 200 kg NPK/Ha with 2 g PPC/1l water. Data were analyzed using ANOVA and proceeded further by Duncan’s test at 5% level. The result of this research showed that utilizing of combination NPK fertilizer with liquid complement fertilizer significant toward plant height, stem circumference, the amount of fruit and not significant toward days to flowering, harvestingage, weight of fresh fruit, and single fruit weight. Treatments of combination 100 kg NPK/Ha with 1 g PPC/1l water showed the best growth and production ca’yenne pepper. Keywords: NPK fertilizer, liquid complement fertilizer, cayenne pepper